Sistem Pendukung Keputusan Pemilihan Mahasiswa Berprestasi Menggunakan Metode MOORA dan MOOSRA - Turiyono, Agus (Journal of Informatics Management and Information Technology, 2026)
Students are students who are studying or completing their education at the tertiary level. Efforts to identify students' talents and interests are crucial for improving human resources. One way to do this is by selecting high-achieving students. In addition to rewarding these high-achieving students, this also serves as motivation for other students to further develop their talents and interests. Efforts to select high-achieving students are still ineffective because the criteria for selecting high-achieving students are based on the assessments of lecturers during teaching. Meanwhile, many other criteria serve as references in selecting high-achieving students. To address this problem, a decision support system is needed to assist in the selection process. The methods used in selecting high-achieving students are the MOORA and MOOSRA methods. The results that can be found in calculating the best alternative as an outstanding student using the MOORA method are students named Septiaman with a value of 0.307. while in the MOOSRA method, the name of Septiaman has a value of 4.165. in the MOORA method, there are the same alternative values, namely Try Yanti and Vessy alwi, each of which has a value of 0.259. while in the MOOSRA method, the values ??of the two alternatives are different, making it easier to determine the best alternative.